Instrumentation for digital nuclear spectroscopy : proceedings of the IAEA technical meeting held in Vienna, Austria, 11-15 October 2010. (IAEA-TECDOC ;, 2013)
"This publication presents the results of an IAEA technical meeting on instrumentation for digital spectroscopy. The meeting provided a forum for discussion of ongoing issues regarding implementation of digital signal processing (DSP) in nuclear spectroscopy. Representatives from industry, research institutes and utilities presented recent experiences with DSP. New opportunities in high resolution spectrometry and the advantages of their application in hand-held field instruments and in remote and unattended nuclear spectrometry systems were also discussed and reviewed."--Publisher's description.